Penerapan Metode Demonstrasi untuk Meningkatkan Hasil Belajar PAI dan Budi Pekerti Peserta Didik Kelas 2 Sekolah Dasar - Moch Ilham Z. A.; Ibnu Muthi (Pusat Riset dan Inovasi Nasional, 2024)
In the life of a Muslim, prayer is the most important part, as spiritual communication to Allah SWT at 5 times every day. The demonstration method allows students to understand the correct steps in performing prayer. Student participation and motivation show positive changes. In the first cycle, the level of student participation increased to 70% during the demonstration process. Students show high interest and active involvement in learning activities. Students' learning motivation has also increased, as can be seen from their enthusiasm in participating in demonstrations and involvement in class discussions. In the second cycle, student participation increased further to 90%. Most students were active in practice and discussion sessions, indicating that this method was successful in creating an interactive and supportive learning environment. Apart from increasing the average score, student participation and motivation also showed positive changes. In the first cycle, the level of student participation increased to 70% during the demonstration process. Students show high interest and active involvement in learning activities. Students' learning motivation has also increased, as can be seen from their enthusiasm in participating in demonstrations and involvement in class discussions. In the second cycle, student participation increased further to 90%. Most students were active in practice and discussion sessions, indicating that this method was successful in creating an interactive and supportive learning environment.